KETERBUKAAN DAN AKUNTABILITAS PEJABAT PUBLIK (Kerangka Pemikiran dan Analisa Kasus Kepegawaian Kota Batu) - Himawan Estu Bagijo (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2007)
Public servant have an abligation to transparent on public policy related to citizen interest. This value is one of the important point in the Democratic Government and Good Governance principles. To apply the principle of transparent and public accountability if is need General principle law of administration (government). The